2002
DOI: 10.1021/ja026111a
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid-Mediated Alumination of Mesoporous Silica and Its Beneficial Effect on Hydrothermal Stability

Abstract: We have investigated the use of supercritical fluids (SCFs) as carriers/solvents during the postsynthesis alumination of mesoporous silica. SCFs were found to be ideally suited for transport of Al into mesoporous silica and to lead to Al-grafted aluminosilicate materials that exhibit exceptional hydrothermal (steam) stability even for highly aluminated materials. The improvements in steam stability arising from the use of SCFs as grafting media (as compared to aqueous or organic solvents) are remarkable, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 15 publications
0
52
0
1
Order By: Relevance
“…To investigate whether or not there was any specific advantage of using the solvents in the supercritical state, an Al-grafted material was synthesized under the equivalent conditions but using liquefied propane instead of SCF propane. [109] This material was found to have lower hydrothermal stability, suggesting that the SCF route led to better dispersion of the Al, a change in the way that the Al interacts with the host silica surface, or a combination of both.…”
Section: Supercritical Fluid-mediated Metallization Of Mesoporous Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether or not there was any specific advantage of using the solvents in the supercritical state, an Al-grafted material was synthesized under the equivalent conditions but using liquefied propane instead of SCF propane. [109] This material was found to have lower hydrothermal stability, suggesting that the SCF route led to better dispersion of the Al, a change in the way that the Al interacts with the host silica surface, or a combination of both.…”
Section: Supercritical Fluid-mediated Metallization Of Mesoporous Silicamentioning
confidence: 99%
“…For example, MCM-41 silica materials have been aluminized by reaction with aluminium isopropoxide using either scCO 2 or supercritical propane as the solvent (reaction temperature = 40 C for CO 2 , 110 C for propane). [109] The samples were then calcined at 600 C for 4 h to obtain the Algrafted materials. [27] Al magic-angle spinning (MAS) NMR spectroscopy indicated that ca.…”
Section: Supercritical Fluid-mediated Metallization Of Mesoporous Silicamentioning
confidence: 99%
“…[22,23] However, the reac- tions have not been adopted commercially because the limited thermal, hydrothermal, and mechanical stabilities of conventional mesoporous sieves, such as the M41S materials, make these supports impractical under typical conditions employed in large-scale industrial applications. In the last few years, improvements in hydrothermal stability of mesoporous silicates have been achieved by the addition of salts during the hydrothermal synthesis (which can improve the degree of condensation of the silicate framework, [24] but sometimes catalyze the collapse of mesopores [25] ), by modification of the sieve surface (to eliminate reactive surface silanol groups) by post-synthesis grafting of aluminum onto such mesostructures, [26] and by increasing the wall thickness. These methods have been reviewed by Liu and Pinnavaia.…”
Section: Improving the Stability Of Mesoporous Sievesmentioning
confidence: 99%
“…[33,34] Because of the low density, low viscosity, low surface tension, and high diffusivity inherent to supercritical fluids, [35] uniform dispersion of functional groups grafted onto the pore walls can be expected. [34,36] It has been reported that a large number of silanol groups are present in hybrid OMMs synthesized via direct synthesis, [37,38] meaning that a grafting reaction could be performed, at least in principle, on these materials to result in bifunctionalized mesoporous materials.…”
Section: Introductionmentioning
confidence: 99%